Disinformation a problem for democracy: profiling and risks of consensus manipulation - Pira, Francesco (Frontiers in Sociology, 2023)
The aims of this article is to analyze in the post-pandemic era of technological wars how platformisation and the opacity that characterizes it can generate manipulative effects on the dynamics of consensus building. We are now in the era of the self-informative program; the hierarchical dimension of sources has vanished in parallel to the collapse of the authority, credibility, and trustworthiness of classical sources. Now, the user creates his own informative program, which gives rise to a new relationship between digital individuals. With this framework in mind, I intend to analyze the narrative of this post-pandemic phase proposed by mainstream media, using the tool of the fake news hexagon, to verify the impact and spread of fake news through social networks where emotionalism, hate speech, and polarization are accentuated. In fact, the definition of the fake news hexagon was the starting point to study through a predefined method the dynamics of proliferation of fake news to activate correct identification and blocking tools, in line with what is defined in the Digital Transformation Institute's manifesto.1 Platforms drive the process of identity construction within containers that adapt to the demands of individuals, leading toward a flattening out of results from web searches as these follow the principle of confirmation bias. We assist to an increasing lack of recognition of the other, the individual moves away from commitment, sacrifice, and achieving a higher collective good. It becomes quite evident how, in the face of the collapse of authority, as this new dimension takes hold, the understanding of reality and the construction of public identity can no longer be the result of the ability to decipher messages alone. Media and social multidimensionality necessitate developing new interpretive processes.